2001
DOI: 10.1046/j.1524-4725.2001.00345.x
|View full text |Cite
|
Sign up to set email alerts
|

Silicone versus Nonsilicone Gel Dressings: A Controlled Trial

Abstract: Silicone and nonsilicone gel dressings are equally effective in the treatment of keloids and hypertrophic scars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0
11

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(81 citation statements)
references
References 37 publications
2
68
0
11
Order By: Relevance
“…The use of silicone dressings is recommended as a safe, non-invasive, simple, and effective method of prophylaxis [18,[22][23][24]. The use of silicone dressings substantially improves the flexibility of old scars as compared to the scars untreated with plasters [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of silicone dressings is recommended as a safe, non-invasive, simple, and effective method of prophylaxis [18,[22][23][24]. The use of silicone dressings substantially improves the flexibility of old scars as compared to the scars untreated with plasters [1].…”
Section: Discussionmentioning
confidence: 99%
“…Most researchers believe that silicone dressings reduce the activity of the capillaries, reduce congestion, and reduce the production of fibroblasts and collagen, causing flattening of the scar. Randomised studies have shown that the use of silicone dressings is effective in improving the colour, size, and hardness of the scar [24]. Treatment of a patient who has a problem with a scar should be selected on the basis of the scar assessment.…”
Section: Discussionmentioning
confidence: 99%
“…28 However, the blinding and the randomization techniques were not reported, and the patients were followed up for only 12 weeks. De Oliveira et al 51 performed a randomized controlled trial in 26 patients who had hypertrophic and keloid scars, and used a combination of silicone gel sheeting, nonsilicone gel sheeting and an untreated control. Their study did not demonstrate any significance in scar size or symptoms with any of the treatments; however, both KD and hypertrophic scars were combined in the analysis, and follow-up measurements occurred after < 6 months.…”
Section: Intralesional Steroid Injectionsmentioning
confidence: 99%
“…4,5,[48][49][50] When used prophylactically on surgical incisions, it can prevent the development of pathologic scars. [51][52][53] Silicone gel sheets were the mainstay of siliconebased treatments until relatively recently. Unfortunately, these sheets could be difficult to use, particularly in large areas, in areas near or over joints, and in areas with high degrees of contour variability, such as the face.…”
Section: Mechanical Therapymentioning
confidence: 99%